PENGARUH REBRANDING, KERAGAMAN PRODUK DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN DI MAKO CAKE & BAKERY DI MARGONDA DEPOK - Reynaldi, Reynaldi; Karla, Eva; Stevianus, Stevianus (Journal of Information System, Applied, Management, Accounting and Research, 2025)
The purpose of this study was to analyze the effect of rebranding, product diversity and price perception on purchasing decisions at Mako Cake & Bakery in Margonda Depok. The analysis method in this study used quantitative primary data, the test stages carried out were: normality test, multicollinearity test, heteroscedasticity test, T test, F test, and coefficient of determination. The data used in this study used a questionnaire instrument and valid data that was successfully collected as many as 100 respondents. The data collection technique used in this study was through a questionnaire. The testing tool used was SPSS software version 25. The results of the study showed that partially the Rebranding variable (X1) with a sig value of 0.000 <0.05, Product Diversity (X2) with a sig value of 0.005 <0.05. and price perception with a sig value of 0.000 <0.05 This means that partially Rebranding, Product Diversity and Price Perception have a positive and significant effect on Purchasing Decisions. Meanwhile, the simultaneous calculation obtained a sig value of 0.000 <0.05. This means that Rebranding, Product Diversity and Price Perception together (simultaneously) have a positive effect on Purchasing Decisions at Mako Cake & Bakery.